Assignment 12

course Mth 163

assignment #012012.

Precalculus I

10-07-2008

......!!!!!!!!...................................

10:12:33

`questionNumber 120000

`q001. Note that this assignment has 3 questions

If we know that y = k x^2, then if (x2/x1) = 7, what is (y2/y1)?

......!!!!!!!!...................................

RESPONSE -->

y2=k(x2)^2/y1=k(x1)^2

y2/y1=(7)^2

y2/y1=49

confidence assessment: 2

.................................................

......!!!!!!!!...................................

10:12:43

`questionNumber 120000

If y2 = k x2^2 and y1 = k x1^2, then y2 / y1 = (k x2^2) / ( k x1^2). Since k / k = 1 this is the same as

y2 / y1 = x2^2 / x1^2, which is the same as

y2 / y1 = (x2 / x1)^2.

In words this tells us if y to is proportional to the square of x, then the ratio of y2 to y1 is the same as the square of the ratio of x2 to x1.

Now if (x2 / x1) = 7, we see that y2 / y1 = (x2 / x1)^2 = 7^2 = 49.

......!!!!!!!!...................................

RESPONSE -->

I got it.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

10:13:01

`questionNumber 120000

`q002. If we know that y = k x^3, then if (x2/x1) = 7, what is (y2/y1)?

......!!!!!!!!...................................

RESPONSE -->

Just cube the 7 in last equation to get 343.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

10:13:10

`questionNumber 120000

If y2 = k x2^3 and y1 = k x1^3, then y2 / y1 = (k x2^3) / ( k x1^3). Since k / k = 1 this is the same as

y2 / y1 = x2^3 / x1^3, which is the same as

y2 / y1 = (x2 / x1)^3.

In words this tells us if y to is proportional to the cube of x, then the ratio of y2 to y1 is the same as the cube of the ratio of x2 to x1.

Now if (x2 / x1) = 7, we see that y2 / y1 = (x2 / x1)^3 = 7^3 = 343.

......!!!!!!!!...................................

RESPONSE -->

I see

self critique assessment: 2

.................................................

......!!!!!!!!...................................

10:13:44

`questionNumber 120000

`q003. If we know that y = k x^-2, then if (x2/x1) = 64, what is (y2/y1)?

......!!!!!!!!...................................

RESPONSE -->

It would be y2/y1=64^-2

y2/y1=2.44

confidence assessment: 2

.................................................

......!!!!!!!!...................................

10:14:08

`questionNumber 120000

If y2 = k x2^-2 and y1 = k x1^-2, then y2 / y1 = (k x2^-2) / ( k x1^-2). Since k / k = 1 this is the same as

y2 / y1 = x2^-2 / x1^-2, which is the same as

y2 / y1 = (x2 / x1)^-2, which is the same as

1 / (x2 / x1)^2, which gives us

(x1 / x2)^2.

So if y = k x^-2, then (y2 / y1) = (x1 / x2)^2.(

In words this tells us if y to is inversely proportional to the square of x, then the ratio of y2 to y1 is the same as the square of the ratio of x1 to x2 (note that this is a reciprocal ratio).

Now if (x2 / x1) = 64, we see that y2 / y1 = (x1 / x2)^2 = (1/64)^2 = 1/ 4096.

......!!!!!!!!...................................

RESPONSE -->

After dividing the final answer on the left, we had the same answer.

self critique assessment: 2

.................................................

"

&#Very good work. Let me know if you have questions. &#